Photocatalytic activity of the thermally oxidized Zn-Ni-, Zn-Co-, Ni-Co-, and Zn-Ni-Co-coated alloy films - DEMİRCİ, SELİM (SPRINGER, 2021)
In this work, Zn-Ni-, Zn-Co-, Ni-Co-, and Zn-Ni-Co-coated alloy films were electrodeposited on titanium substrate. The coated alloy films were annealed in order to form oxides at 800 degrees C in air for 2 h. The crystalline structures, surface morphologies, and chemical composition of the samples were examined using X-ray diffraction techniques (XRD), scanning electron microscopy (SEM), and (EDX). Photocatalytic performance of samples was performed by means of the degradation of methylene blue (MB) under UV irradiation. The SEM results showed that the different morphologies such as needle-shaped nanowires, grains, and pores were formed on the surface. The results showed that the photocatalytic performance of the samples demonstrated differences according to alloy type. The Zn-Ni alloy coating exhibited better photocatalytic activity. Photocurrent measurements illustrated that Zn-Ni sample possessed the highest suppression of photogenerated charge carrier recombination and lowest charge transfer resistance (R-ct) layer. It is expected that this work could provide a promosing way for fabricating Zn-based photocatalyts in environmental redemediation.
Keywords: Electrodeposition; Coated alloy film; Thermal annealing; Surface morphology; Photocatalytic activity; DEGRADATION; ELECTRODEPOSITION; PERFORMANCE; COATINGS